Penilaian Bangunan Masjid Tua Wapauwe di Desa Kaitetu, Maluku - Tekat Dwi Cahyono; Fitriyanti Kaliky; Narti Kawarnidi (Jurnal Ilmu Pertanian Indonesia, 2018)
Historical tour is one of supporting aspects in tourism industry, locally and nationally. Old mosque of Wapauwe at Kaitetu Village of Central Maluku Regency, Maluku Province, is one of historical tour destinations that offers beautiful architecture and wood structure. Even though the main building is only 10 x 10 m2, this is one of important relics of Maluku’s Islamic culture richness that stands and is well maintained since its building in 1414 AD. A structure surely will deteriorate during utilization, therefore a study on the durability of old Wapauwe Mosque building was conducted. Forensic method was employed in all of building components and the results were subsequently compared in the standard of proper building. The results revealed that the building was still in well category and fit for proper use. The structure of columns, walls, and roof frame were still quite sturdy and well maintained, yet symptoms of water capillarity were appeared on few parts of the walls and building foundation. The building was built from several wood species namely Nani (Xanthostemon verus), Linggua (Pterocarpus indicus), Red meranti (Shorea pinanga) and Bintanggur (Calophyllum inophyllum). The study recommends a moderate maintenance is required in roof that was noticeably suffered a little damage and particular method on preventing and inhibiting dampness on walls and foundation. Moreover, subsequent study will be required in wood anatomy structure, creep test and wood ages in determining wood durability in longer term.